'Moral Factors' in British military thought and doctrine, 1856–1899. (April 2022) - Samuels, Martin
During the second half of the nineteenth century, the introduction of new weaponry dramatically changed the balance between moral factors and technology on the battlefield. Yet, this shift was widely met by a renewed emphasis on the importance of the human element. This article explores the development of thinking on this issue in the British Army during the period from 1856 to 1899. This reveals three phases, representing the struggle between the conservative Duke of Cambridge and the modernizing Lord Wolseley, with their view explored through the writings of key theorists and in the official manuals. This reveals that the Duke remained focused on a mechanical model, centred on the teachings of Jomini, where the troops were simply tools in the hands of their commanders, whereas Wolseley emphasized the need to protect the 'moral strength' of the troops and saw undermining that of the enemy as the key to victory, yet always recognizing that bravery and resilience could never overcome modern weaponry.